Rural‐urban disparities in health status among US cancer survivors1. Issue 5 (23rd October 2012) - Weaver, Kathryn E.; Geiger, Ann M.; Lu, Lingyi; Case, L. Douglas
Abstract BACKGROUND: Although rural residents are more likely to be diagnosed with more advanced cancers and to die of cancer, little is known about rural‐urban disparities in self‐reported health among survivors. METHODS: The authors identified adults who had a self‐reported history of cancer from the National Health Interview Survey (2006‐2010). Rural‐urban residence was defined using US Census definitions. Logistic regression with weighting to account for complex sampling was used to assess rural‐urban differences in health status after accounting for differences in demographic characteristics. RESULTS: Of the 7804 identified cancer survivors, 20.8% were rural residents. This translated to a population of 2.8 million rural cancer survivors in the United States. Rural survivors were more likely than urban survivors to be non‐Hispanic white (P < .001), to have less education (P < .001), and to lack health insurance (P < .001). Rural survivors reported worse health in all domains. After adjustment for sex, race/ethnicity, age, marital status, education, insurance, time since diagnosis, and number of cancers, rural survivors were more likely to report fair/poor health (odds ratio, 1.39; 95% confidence interval, 1.20‐1.62), psychological distress (odds ratio, 1.23; 95% confidence interval, 1.00‐1.50), ≥2 noncancer comorbidities (odds ratio, 1.15; 95% confidence interval, 1.01‐1.32), and health‐related unemployment (odds ratio, 1.66; 95% confidence interval, 1.35‐2.03). CONCLUSIONS: The current results provide the first estimates of the proportion and number of US adult cancer survivors who reside in rural areas. Rural cancer survivors are at greater risk for a variety of poor health outcomes, even many years after their cancer diagnosis, and should be a target for interventions to improve their health and well being. Cancer 2013. © 2012 American Cancer Society.